REMEMBERING XIAO SHAN IN BA JIN ESSAYS THE WOUNDS OF THE CULTURAL REVOLUTION - Nadira Alkaff; Hin Goan Gunawan (Fakultas Sastra Universitas Darma Persada, 2020)
The Cultural Revolution era was a dark period in Chinese history. The resistance to the power of Chairman Mao by literati people has resulted in deep wounds, as a result of intimidation, bad stigma, exclusion, and even imprisonment which often ends in death. Ba Jin's essay Remembering Xiao Shan can be seen as a mirror reflecting the deep wounds experienced by the author who is accused of being part of a counterrevolutionary group. Not only himself, but his beloved wife also had to bear the wounds of the Cultural Revolution. This study uses a hermeneutical analysis model to explore the author's